2020
DOI: 10.1038/s41467-020-19744-3
|View full text |Cite
|
Sign up to set email alerts
|

The human impact on North American erosion, sediment transfer, and storage in a geologic context

Abstract: Humans are primary agents of geomorphic change, and rates of anthropogenic landscape change likely far exceed the pace of change expected from natural geologic processes. Nevertheless, our understanding of the impact of humans on the natural landscape is limited by difficulties in accurately comparing past and present rates of change across wide spatial and temporal scales. Here, we present a compilation of  >4000 rates of alluvial sediment accumulation that provide an indirect record of North American eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 42 publications
(115 reference statements)
3
36
1
1
Order By: Relevance
“…and may have different impacts on erosion, our results strongly point to the overwhelming impact of agriculture and related activities on short-term erosion rates, corroborating previous work (Dedkov and Mozzherin, 1996;Montgomery, 2007;Wilkinson and McElroy, 2007;Kemp et al, 2020). However, it is worth noting that the difference in short-term erosion rates between anthropogenic and non-anthropogenic regions shown here is smaller than was shown in previous studies (Dedkov and Mozzherin, 1996;Montgomery, 2007;Wilkinson and McElroy, 2007;Kemp et al, 2020). For example, Dedkov and Mozzherin (1996) estimated that anthropogenic activities increase sediment yields by a factor of 3.5 in large rivers and 8 in small rivers.…”
Section: Anthropogenic Influence On Short-term Erosion Ratessupporting
confidence: 91%
See 4 more Smart Citations
“…and may have different impacts on erosion, our results strongly point to the overwhelming impact of agriculture and related activities on short-term erosion rates, corroborating previous work (Dedkov and Mozzherin, 1996;Montgomery, 2007;Wilkinson and McElroy, 2007;Kemp et al, 2020). However, it is worth noting that the difference in short-term erosion rates between anthropogenic and non-anthropogenic regions shown here is smaller than was shown in previous studies (Dedkov and Mozzherin, 1996;Montgomery, 2007;Wilkinson and McElroy, 2007;Kemp et al, 2020). For example, Dedkov and Mozzherin (1996) estimated that anthropogenic activities increase sediment yields by a factor of 3.5 in large rivers and 8 in small rivers.…”
Section: Anthropogenic Influence On Short-term Erosion Ratessupporting
confidence: 91%
“…Previous studies have shown that, in some regions, short-term erosion rates are higher than long-term rates because of recent human activities (Clapp et al, 2000;Gellis et al, 2004;von Blanckenburg, 2006;Kemp et al, 2020) or climatic change https://doi.org/10.5194/esurf-2021-7 Preprint. Discussion started: 24 February 2021 c Author(s) 2021.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations